Privatising Development : Transnational Law, Infrastructure and Human Rights. - Likosky, Michael B. (BRILL, 2005)
This book looks at the shift since the 1980s away from state-financed and towards privatised international infrastructure projects. An interdisciplinary group of contributors look at the relationship between privatisation and human rights in diverse national settings and in multiple sectors of the economy. These issues are explored through international organisation frameworks and internal politics, legislative guides, contracts, and public-private organisations. The role of the World Bank, MIGA, export credit agencies, the UN Commission on International Trade Law, credit ratings agencies, international banks, TNCs, NUDs, community groups and state agencies are examined.